PERBEDAAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN STRATEGI PEMBELAJARAN INKUIRI TERHADAP HASIL BELAJAR IPA KELAS V SDN KEBON BARU - Andriana, Encep; Nulhakim, Lukman; Nurlia Ningsih, Ade (LPPM Universitas Bina Bangsa, 2024)
This study aims to determine the effect of science learning outcomes for fifth grade students using inquiry learning strategies using conventional learning strategies and to determine the fifth-grade science learning outcomes using inquiry learning strategies are higher than students using conventional learning strategies. This research was conducted at SD Negeri Kebon Baru, Mauk District, Tangerang Regency, with the research subjects being fifth grade students consisting of 2 classes, namely VA and VB classes consisting of 27 students. This type of research uses the Quasi Experimental method (quasi-experimental). The instruments used in this study were tests to measure learning outcomes and questionnaires to measure student learning activities. Based on the results of the analysis and discussion, it can be found that there are differences in student learning outcomes of science lessons in the experimental group taught by the Inquiry learning model which is quite good. It can be seen from the average value of the posttest results of the experimental class, which is 77, which is higher than the control class, which is 66.02. This shows that there are differences in students' cognitive learning outcomes after being given treatment in the form of applying the inquiry learning model.